Specific Conditions for Resveratrol Neuroprotection against Ethanol-Induced Toxicity - Brigitte Gonthier; Nathalie Allibe; Cécile Cottet-Rousselle; Frédéric Lamarche; Laurence Nuiry; Luc Barret (Journal of Toxicology)
Aims. 3,5,4′-Trihydroxy-trans-stilbene, a natural polyphenolic compound present in wine and grapes and better known as resveratrol, has free radical scavenging properties and is a potent protector against oxidative stress induced by alcohol metabolism. Today, the mechanism by which ethanol exerts its toxicity is still not well understood, but it is generally considered that free radical generation plays an important role in the appearance of structural and functional alterations in cells. The aim of this study was to evaluate the protective action of resveratrol against ethanol-induced brain cell injury. Methods. Primary cultures of rat astrocytes were exposed to ethanol, with or without a pretreatment with resveratrol. We examined the dose-dependent effects of this resveratrol pretreatment on cytotoxicity and genotoxicity induced by ethanol. Cytotoxicity was assessed using the MTT reduction test. Genotoxicity was evidenced using single cell gel electrophoresis. In addition, DNA staining with fluorescent dyes allowed visualization of nuclear damage using confocal microscopy. Results. Cell pretreatment with low concentrations of trans-resveratrol (0.1–10 μM) slowed down cell death and DNA damage induced by ethanol exposure, while higher concentrations (50–100 μM) enhanced these same effects. No protection by cis-resveratrol was observed. Conclusion. Protection offered by trans-resveratrol against ethanol-induced neurotoxicity was only effective for low concentrations of this polyphenol.